Analysis of The Influence of E-Commerce Use and Digital Literacy Toward Society Intention in Digital Entrepreneurship - Nur Augus Fahmi; Zulkifli Zulkifli; Tito Irwanto; Apit Fathurohman; I Wayan Adi Pratama (Institut Riset dan Publikasi Indonesia, 2023)
The purpose of this study is to examine the relationship between students' interest in digital entrepreneurship and their use of digital literacy and e-commerce. Quantitative research is the method used in this study. This study uses correlational data collection methods. In this study, questionnaires are used to collect the data. In the questionnaire method, the validity and reliability of the questionnaire will be examined in advance. Data processing will be done using statistical methods after data collecting is finished. To use multiple regression analysis to examine the impact of each variable. Students make up the study's population. With a sample size of 200 participants, the researchers used a basic random sampling procedure. According to the study's findings, students' interest in digital entrepreneurship was positively impacted by their level of digital literacy. Students' interest in digital entrepreneurship is positively impacted by the use of e-commerce. The use of e-commerce and digital literacy both increase students' interest in digital entrepreneurship.